POLA TRANSFORMASI FATWA EKONOMI SYARIAH DSN-MUI DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Wahid, Soleh Hasan (Ahkam: Jurnal Hukum Islam, 2016)
Until now, there have been 100 fatwas issued by the DSN-MUI. In ayah (3) of Law No. 21/2008 concerning Islamic Banking, it is explained that the fatwa referred in ayah (2) set forth in Indonesia. That case consist that Bank Regulation implies that the new DSN-MUI fatwa is binding after being regulated become Bank Indonesia Regulation (PBI). In transformed into PBI, fatwa DSN-MUI has been also transformed into the Economic Law Compilation true Syariâah is the Indonesian Supreme Court Regulation No. 2 of 2008. In addition the DSN-MUI fatwa also transformed into provisions of the legislation in the field of capital markets such as the Law No. 19 of 2008 concerning Sharia Securities. There was a lot of research about the kinds of fatwa that are transformed into positive law mentioned above, but not touching the whole aspect of how the pattern of absorption DSN-MUI fatwa to the laws and this research was conducted to answer the question. This study is using research library with content models and comparative analysis in order to explain the contents of the statutory provisions and DSN-MUI fatwa and to compare both of them. Based on this research we concluded that there are three models DSN-MUI fatwa absorption in the legislation, the first model of copy and paste or copy the title fatwa in the articles of a law. Second, substantive patterns that only take substance from the fatwa was later translated into chapterâs legislation with language that formal. Third, extending the provision of the fatwa and/or translating the provisions of the fatwa of a general nature in the form of a more operational so that it can be applied in the operations of a financial institution.Kata kunci: Transformasi Fatwa, Ekonomi Syariah, DSN-MUI,Perundang-Undangan